Family Health Strategy and its interference in hospitalizations sensitive to primary health care (Research, Society and Development, 2020)
The present study sought to analyze the interference of the Family Health Strategy in Hospitalizations due to Conditions Sensitive to Primary Care. It is an integrative review of the literature published in the period 2013-2018, with the following research questions: is it possible to use the indicator Hospitalization for Conditions Sensitive to Primary Care to assess this level of care? Can the Family Health Strategy contribute to reducing these hospitalizations? 35 articles were selected for analysis. The identification and selection of the studies was carried out by searching for publications indexed in the database of the Virtual Health Library (VHL) and Capes Portal in the months of May and June 2019. It was found that this indicator was used as one of the variables for the evaluation of the Family Health Strategy. It is understood that this strategy, alone, will not impact the reduction of this indicator. Still, research indicates that its expansion is associated with a reduction in hospitalizations sensitive to primary care. Therefore, it is necessary to invest in Family Health and in the reorganization of its work process, so that it is effectively the coordinator of care at the primary level of care, enabling improvement in health indicators.